Does Cooperation between Finnish Forest Owners Increase Their Interest in Capercaillie (Tetrao Urogallus) Lekking Site Management?. Issue 11 (2nd November 2022) - Ikonen, Piia; Miettinen, Janne; Haara, Arto; Matala, Juho; Hujala, Teppo; Mehtätalo, Lauri; Pappinen, Ari
Abstract: This research reviews the factors that are associated with the willingness of forest owners to participate in cross-boundary management of capercaillie ( Tetrao urogallus ) lekking sites. The data were collected with a double-sampling survey that was targeted at Finnish forest owners. Our findings infer that forest owners are quite often willing to participate in cooperative actions, and most interestingly, the opportunity for cooperation seems to increase the interest of forest owners to manage lekking sites. However, achievement of an ecologically and socially valuable cooperative solution would require finding forest owners with similar objectives and properties with suitable ecological values. Our results provide important evidence of how cooperation can inspire forest owners in natural resource management, which will also provide benefits to the wider socio-ecological system.